Low-energy dielectric screening in Pd and PdHx systems; Journal of Physics: Condensed Matter; Vol. 27, iss. 5 - Silkin V. M. Vyacheslav Mikhaylovich; Chernov I. P. Ivan Petrovich; Sklyadneva I. Yu. Irina Yuryevna; Chulkov E. V. Evgeny Vladimirovich; Nazarov V. U. Vladimir (2015, 2015)
Title screen